2015
DOI: 10.4103/0253-7613.150317
|View full text |Cite
|
Sign up to set email alerts
|

Lead-induced adverse effects on the reproductive system of rats with particular reference to histopathological changes in uterus

Abstract: Objectives:This study was undertaken to elucidate the adverse effect of lead on female reproductive system following in vivo exposure in rats.Materials and Methods:Animals of Group II, III and IV received lead acetate in drinking water (30, 100 and 300 ppm, respectively) for 28 days whereas Group I served as control. Lead levels in digested blood and bone samples were measured using atomic absorption spectrophotometer.Results:Marked and a significant decrease in per cent body weight gain was observed in rats o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…A reduction in feed and fluid intake was obvious in animals treated only with the toxicants compared to the rats given deionized water. This observation is in line with the study of Nakade et al [ 18 ]. Obviously from the result, a decrease in appetite for water and food may be a result of heavy metal poisoning.…”
Section: Discussionsupporting
confidence: 94%
“…A reduction in feed and fluid intake was obvious in animals treated only with the toxicants compared to the rats given deionized water. This observation is in line with the study of Nakade et al [ 18 ]. Obviously from the result, a decrease in appetite for water and food may be a result of heavy metal poisoning.…”
Section: Discussionsupporting
confidence: 94%
“…Animals exposed to mercury showed uterus inflammatory cells in the endometrium and myometrium [ 170 ]. The uterine endometrial area was decreased compared to control, while the myometrium area showed no difference between the groups [ 170 ].…”
Section: Mercury (Hg)mentioning
confidence: 99%
“…Lead is a toxic heavy metal and poses serious health risks including abnormalities of male and female reproductive systems (4–7), neurological disorders (4, 8), DNA damage, and chromosomal abnormalities (9, 10) leading to carcinogenesis (3, 4). To minimize the risk to children, the CPSC may also consider further lowering the permissible level of lead in products for children.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Based on the assumptions described above, we conclude that the crayons containing 99 ppm of lead, a level at which the crayons comply with the CPSC regulation under the CPSIA, will require labeling under the California Proposition 65, the Safe Drinking Water and Toxic Enforcement Act of 1986, as a reproductive toxin. Lead is a toxic heavy metal and poses serious health risks including abnormalities of male and female reproductive systems ( 4 – 7 ), neurological disorders ( 4 , 8 ), DNA damage, and chromosomal abnormalities ( 9 , 10 ) leading to carcinogenesis ( 3 , 4 ). To minimize the risk to children, the CPSC may also consider further lowering the permissible level of lead in products for children.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation